2012
DOI: 10.1093/ageing/afs033
|View full text |Cite
|
Sign up to set email alerts
|

High normal plasma triglycerides are associated with preserved cognitive function in Chinese oldest-old

Abstract: we concluded that high normal plasma triglyceride was associated with preservation of cognitive function while lower concentrations were not in the Chinese oldest-old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 29 publications
8
67
0
1
Order By: Relevance
“…Further, in a 26 year follow-up study of elderly, serum cholesterol levels decreased in elderly who developed mild cognitive impairment, while increased in those who maintained normal cognition in Asian elderly (12). Moreover, our previous study found a significant association between high normal plasma TG and preserved cognitive function in the Chinese oldest old (13), which was also confirmed in this study. There was also emerging evidence that cholesterol-lowering therapy was associated with some adverse effects on cognitive function in rodents (27) and human (28).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Further, in a 26 year follow-up study of elderly, serum cholesterol levels decreased in elderly who developed mild cognitive impairment, while increased in those who maintained normal cognition in Asian elderly (12). Moreover, our previous study found a significant association between high normal plasma TG and preserved cognitive function in the Chinese oldest old (13), which was also confirmed in this study. There was also emerging evidence that cholesterol-lowering therapy was associated with some adverse effects on cognitive function in rodents (27) and human (28).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, previous research indicated that higher consumption of tea, which is linked to lower cholesterol level, was proved to take a protective effect on cognition (7), and higher cholesterol was linked to faster cognitive decline among patients with Alzheimer's disease (8). In contrast, other studies provide contradictory findings that demonstrated no association between cholesterol concentrations and cognitive impairment or dementia (9,10), and even that higher concentrations of cholesterol were associated with a decreased risk of cognitive impairment among the elderly (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leisure activities included growing flowers, raising pets, reading books, playing cards, watching TV and listening to the radio, it was defined as ‘yes’ if the frequency of any item above is once per week or more. Social activities included support of housekeeping and taking part in organized social activities, and it was defined in the same way with leisure activities (18). Resilience was assessed by a simplified resilience score emphasizing coping and adjusting among the elderly and reflecting personal tenacity, optimism, coping with negative mood, secure relationship, and self-control (20), with the higher scores reflecting greater resilience, and higher resilience defined as a score ≥16.…”
Section: Methodsmentioning
confidence: 99%